Assessment of existing bicycle facilities in private and public universities in Klang valley - Ramli M.Z.; Aziz N.A.A.; Hamid N.B.; Azman N.S.; Razman R.; Zawawi M.H.; Ismail I.N. (American Institute of Physics Inc., 2023)
Transportation is one of a major contributor in emissions of carbon dioxide (CO2) gases. Citizens in Malaysia mostly prefer to drive their own private vehicle as Malaysia has gained an advance urbanization since 1990s. Providing bicycle facilities is crucial in order to encourage people to use bicycle as their mode of transportation. Even though some universities have already implemented the bicycle initiatives and provided the facilities to their students, there is no well-established guideline in Malaysia for bicycle facilities. Therefore, the main objective of this study was to assess the existing bicycle facilities based on established guidelines from developed countries and standards used in designing the existing facilities. Two universities from public and private university were selected for the physical assessment. A physical assessment was done by using developed scoring system which based on requirements stated in the guidelines. The finding shows that University A get good in overall score which is 74.71% while University B acquired moderate in overall score which is 50.08%. 2018 Author(s).